2022
DOI: 10.3389/fonc.2022.878675
|View full text |Cite
|
Sign up to set email alerts
|

IL1 Pathway in HPV-Negative HNSCC Cells Is an Indicator of Radioresistance After Photon and Carbon Ion Irradiation Without Functional Involvement

Abstract: BackgroundTreatment of locally advanced HPV-negative head and neck squamous cell carcinoma (HNSCC) with photon radiation is the standard of care but shows only moderate success. Alterations in response toward DNA DSB repair, apoptosis, and senescence are underlying determinants of radioresistance in the tumor cells. Recently, senescence and the associated secretory phenotype (SASP) came into the focus of research and raised the need to identify the tumor-promoting molecular mechanisms of the SASP. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…IL1b is increased in a variety of malignancies, and it is well recognized that patients with overproduction of IL1b have poorer prognosis. Also, it has been demonstrated that IL1b is an indicator of cellular radioresistance and senescence in HNSCC cells without functional involvement in these processes [ 16 ]. In our study we saw a higher IL1b transcript level in both age groups (≤ 60 and > 60) and locations (larynx and oral cavity) in men but not women, in all histologic grade stages (G1-G3) and T3-T4 and N0, N2 TNM tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…IL1b is increased in a variety of malignancies, and it is well recognized that patients with overproduction of IL1b have poorer prognosis. Also, it has been demonstrated that IL1b is an indicator of cellular radioresistance and senescence in HNSCC cells without functional involvement in these processes [ 16 ]. In our study we saw a higher IL1b transcript level in both age groups (≤ 60 and > 60) and locations (larynx and oral cavity) in men but not women, in all histologic grade stages (G1-G3) and T3-T4 and N0, N2 TNM tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…IL1B can promote tumor-promoting inflammation in breast cancer, and it can be targeted in metastatic breast cancer patients with a soluble IL1 receptor antagonist, and also can be an immunomodulatory target in treatment-resistant breast cancer [ 52 ]. IL1 pathway is strongly induced by irradiation and correlate with radioresistance and senescence, especially IL1A and IL1B which exhibit excellent associations [ 53 ]. Our cell-cell communication network identified a strong association of the IL1 pathway with the macrophages, suggesting that the IL1 pathway might be involved in CESC CCRT resistance.…”
Section: Discussionmentioning
confidence: 99%
“…nasal cavity, ear) [12] or in second-line treatment [16][17][18] with good clinical results that argue for a broader clinical practice. Moreover, the multifaceted mechanisms of therapy resistance, exhibited by HNSCC tumors, such as inflammatory and immune-modulating cytokine and chemokine signaling or overstimulation of the PI3K/AKT/TOR signaling pathway are alleviated for carbon ion irradiation [19,20]. In this context, [15] is a valuable source to plan further clinical studies.…”
Section: Radiation Biologymentioning
confidence: 99%